Digital Pedagogy in Wind Instrument Learning: Integrating Visual Micro-Skills for Correcting Technical Misconceptions in Trumpet Performance - Ibnu Syahruroji Fiqriannur; Setya Yuwana Sudikan; Trisakti; Anik Juwariyah; Harpang Yudha Karyawanto; Grace Natalie (Universitas Negeri Medan, 2026)
This study aims to analyze the role of visual micro-skills in digital pedagogy for correcting misconceptions in trumpet playing techniques at the micro-level of motor skills, particularly in the coordination of embouchure, airflow, and breathing control. The study employs a mixed-methods approach within a design-informed pedagogical inquiry framework. A total of 25 participants were involved in a visual micro-skill-based learning intervention. Quantitative data were obtained through pre-test and post-test, while qualitative data were collected through observation, reflection, and literature review, and subsequently analyzed using paired sample t-tests and thematic analysis. The results show that the integration of video-based visual micro-skills significantly improves micro-level technical skills in trumpet playing (62.00 to 84.72; p < 0.001). Video visualization operated through close-up, slow motion, replay, and pausing clarifies techniques while revealing the coordination of embouchure, airflow, and breathing control that was previously implicit, thereby shifting learning from mechanical imitation toward reflective understanding that integrates visual perception, cognition, and motor response. These findings indicate a shift in learning from mere imitation toward a reflective-analytical process that systematically integrates visual perception, cognition, and motor response. Theoretically, this study strengthens the position of visual micro-skills as a conceptual framework for explaining technique learning at the micro level, while practically providing a foundation for developing trumpet instruction that is more accurate, adaptive, and capable of minimizing technical errors from the early stages.